Considerations when investigating lncRNA function in vivo - Bassett, A; Akhtar, A; Barlow, D; Bird, A; Brockdorff, N; Duboule, D; Ephrussi, A; Ferguson-Smith, A; Gingeras, T; Haerty, W; Higgs, D; Miska, E; et al. (eLife Sciences Publications, 2014)
Although a small number of the vast array of animal long non-coding RNAs (lncRNAs) have known effects on cellular processes examined in vitro, the extent of their contributions to normal cell processes throughout development, differentiation and disease for the most part remains less clear. Phenotypes arising from deletion of an entire genomic locus cannot be unequivocally attributed either to the loss of the lncRNA per se or to the associated loss of other overlapping DNA regulatory elements. The distinction between cis- or trans-effects is also often problematic. We discuss the advantages and challenges associated with the current techniques for studying the in vivo function of lncRNAs in the light of different models of lncRNA molecular mechanism, and reflect on the design of experiments to mutate lncRNA loci. These considerations should assist in the further investigation of these transcriptional products of the genome.